Algebraic and computer-based methods in the undirected degree/diameter problem - A brief survey - Hebert Perez-Roses (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2014)
This paper discusses the most popular algebraic techniques and computational methods that have been used to construct large graphs with given degree and diameter.